The Jeremiad in American Science Fiction Literature, 1890-1970 - (:unkn) unknown (My University, 2019)
Scholarship on the form of sermon known as the American jeremiad—a prophetic warning of national decline and the terms of promised renewal for a select remnant—draws heavily on the work of Perry Miller and Sacvan Bercovitch. A wealth of scholarship has critiqued Bercovitch’s formulation of the jeremiad, which he argues is a rhetorical form that holds sway in American culture by forcing political discourse to hold onto an “America” as its frame of reference. But most interlocutors still work with the jeremiad primarily in American studies or in terms of national discourse. Rooted in the legacy of Puritan rhetoric, the jeremiad is most commonly used to frame discussion of political speech or literary texts that grapple with national identity. The jeremiad is also firmly entrenched in science-fiction literature, and some attempts have been made to assay its function in that genre. But studies of the jeremiad in science-fictional literature tend toward framing those works, too, in terms of national discourse, even though science-fictional literature typically relies on tropes and strategies that are far beyond the ability of nationality to contain. In this dissertation, I argue that the jeremiad in science-fictional American literature works against the framework of national identity. Though the texts draw on contemporary political discourses that are often specifically American, their engagements with the jeremiad lead them beyond the imaginary of the United States. Instead, by examining specific science-fictional approaches to the concepts of time and space, race, technocracy, and images of exodus, I demonstrate that these texts consistently urge readers to imagine political belonging outside the framework of national culture. After examining the science-fictional approaches to these concepts and how we can best understand them in terms of the jeremiad, I put them together to show that, even in an American literary context, the American jeremiad militates against cohesion, generating different vectors of political action within and without the American paradigm.
Keywords: American literature; jeremiad; prophecy; science fiction; twentieth century; utopian studies